Financial appraisal of layer production in Peninsular Malaysia - Masan, Ilmas Abdurofi; Ismail, Mohd Mansor; Gabdo, Bashir Hamman (Global Advanced Research Journals, 2018)
In Malaysia, egg production is a crucial necessity that the demand proceeds tremendously to the society. Due to the lack of food supply and the farmers are still not be able to get more profit, several agricultural policies have been introduced by Malaysian government in order to additionally boost the performance of agricultural sector and fulfill the government’s target to reach closely self-sufficiency. One of the common scheme of government incentives is offered by reducing the tax obligation from the income statement that usually imposed to the commercialized company. Nevertheless, less information of promoting on tax scenarios, ineffectiveness of applying the incentive program and scant encouragement to potential investor are still remain untouched. Therefore, the main objective of this study is to investigate the role of government incentives in effecting project assessment of layer industry in different technology. The indicators of capital budgeting analysis namely Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (PI) and Payback Period (PBP) are explained to illustrate financial appraisal. The study reveals that the layer firms which involve in the open and close systems are financially viable to be a proposed project. Moreover, the industry represents extremely financial attractiveness and rapidly recover its financial investment where the government provides incentives as tax exemption.